Alan P. Merriam versus Mantle Hood dalam Orientasi Studi Etnomusikologi - Slamet Riyadi (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2002)
The anthropological and musicological approaches of ethnomusicology have been extensively discussed by ethnomusicologists. In revealing musical facts, the anthropoÂlogical approach tends to discern music as a human behavior phenomenon. Meanwhile, the musicological approach considers music as exclusively musical matter.